Chloramine Concentrations within Distribution Systems and Their Effect on Heterotrophic Bacteria, Mycobacterial Species, and Disinfection Byproducts. (15th October 2021) - Pfaller, Stacy; King, Dawn; Mistry, Jatin H.; Alexander, Matthew; Abulikemu, Gulizhaer; Pressman, Jonathan G.; Wahman, David G.; Donohue, Maura J.
Highlights: The measured monochloramine residual did not indicate the water's microbial quality. At locations beyond the entry point (EP), the microbial counts were 2+ logs higher. 65 to 100% of the average THM/HAA formation occurred before the EP location. M. abscessus and  M. intracellulare (MI) were prevalent throughout the distribution. Distribution and "at tap" MI concentrations were equivalent (10 3 GU/L). Abstract: Chloramine is a secondary disinfectant used to maintain microbial control throughout public water distribution systems. This study investigated the relationship between chloramine concentration, heterotrophic bacteria, and specific Mycobacterium species. Sixty-four water samples were collected at four locations within the utility's distribution network on four occasions. Water samples were analyzed for total chlorine and monochloramine. Traditional culture methods were applied for heterotrophic bacteria and nontuberculous mycobacteria (NTM), and specific quantitative polymerase chain reaction (qPCR) assays were used to detect and quantify Mycobacterium avium,   M. intracellulare, and  M. abscessus . Total chlorine and monochloramine concentrations decreased between the distribution entry point (4.7 mg/L and 3.4 mg/L as Cl2, respectively) to the maximum residence time location (1.7 mg/L and 1.1 mg/L as Cl2, respectively). Results showed that heterotrophic bacteria and NTM counts increased by two logs as the water reached the average residence time (ART) location. Microbiological detection frequencies among all samples were: 86% NTMs, 66% heterotrophic bacteria, 64% M. abscessus, 48% M. intracellulare, and 2% M. avium . This study shows that heterotrophic bacteria and NTM are weakly correlated with disinfectant residual concentration, R 2 =0.18 and R 2 =0.04, respectively. Considering that specific NTMs have significant human health effects, these data fill a critical knowledge gap regarding chloramine's impact on heterotrophic bacteria and Mycobacterial species survival within public drinking water distribution systems. Graphical Abstract: Image, graphical abstract